HUBUNGAN LAMANYA PAPARAN SINAR MATAHARI DENGAN KEJADIAN MELASMA PADA WANITA PEMULUNG DI TEMPAT PEMBUANGAN AKHIR TELAGA PUNGGUR KOTA BATAM - Dyah Marianingrum; Sudarsono . (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2019)
Melasma is one of the most common skin problems, because it causes facial skin disorders as well as a decrease in the confidence of sufferers, in the form of uneven hyperpigmentation macules which are generally symmetrical. The exact incidence of melasma is still unknown, including non-communicable diseases which are one of the occupational diseases. The purpose of this study was to determine the relationship between the duration of sun exposure with the incidence of melasma in female scavengers in the final dumpsite of Telaga Punggur Batam City. This study was an observational analytic study with a cross-sectional design, which was conducted in December 2019. Data was taken from respondents to fill in the questionnaire, including sunlight. Sample collection using sloven formula with random sampling techniques of 60 respondents. This study shows that respondents who suffer from melasma are 39 respondents (65.0%), while respondents who do not suffer from melasma are 21 respondents (35.5%). Respondents who were exposed to sunlight <3 hours / day were 20 respondents (33.3%), while those who were exposed> 3 hours / day were 40 respondents (66.7%). With statistical tests using chi-square, there is a significant relationship between the duration of sun exposure with the incidence of melasma in scavenger women with a p-value = 0.001 (p <0.05). RR = 7.429, with this value it can be interpreted that the length of sun exposure has a risk of 7 times for the occurrence of melasma. From the results of the study, it can be concluded that there is a relationship between the length of sun exposure and the incidence of melasma.